Leadership and Dividend Policy in Emerging Markets: A Systematic Literature Review and Conceptual Framework - Melli, Melli; Wardi, Yunia; Rusdi, Rino (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2026)
This systematic literature review examines how leadership-related factors are positioned in the literature alongside established financial determinants of dividend policy in emerging markets. Following PRISMA guidelines, the study reviews 26 peer-reviewed articles published between 2015 and 2025 and synthesizes evidence related to profitability, capital structure, leadership styles, corporate governance, and ESG practices. The findings confirm that profitability (ROA) and capital structure (DER) remain the most robust and consistently supported determinants of dividend policy, in line with established corporate finance theories. Evidence linking leadership styles to dividend decisions is limited and fragmented, with leadership primarily discussed as a contextual or complementary factor influencing managerial preferences rather than as a primary explanatory variable. From a theoretical perspective, this review clarifies the boundaries of current dividend policy theory by situating leadership as a conditioning construct operating through governance and ethical considerations, rather than as an independent determinant. From a practical perspective, the findings suggest that managers and boards in emerging markets should interpret dividend decisions not only through financial performance indicators but also within broader governance and leadership contexts, particularly when balancing payout stability and long-term investment priorities. The proposed conceptual framework remains exploratory and highlights the need for future empirical studies using longitudinal data and rigorous econometric methods to assess the moderating role of leadership in dividend policy decisions.